Scrutinizing Social Identity Theory in Corporate Social Responsibility: An Experimental Investigation - Paruzel, Agnieszka; Danel, Martin; Maier, Günter W. (Frontiers in Psychology, 2020)
Social identity theory is often used to explain the relationship between corporate social responsibility (CSR) and employee-related outcomes, but until now, a sound empirical examination is lacking, and causality remains unclear. CSR can unfold its effect mainly because of three theoretically important aspects of CSR initiatives, which increase identification, i.e. distinctiveness, prestige, and salience of the out-group. This study examines how far social identity theory can explain the effect of CSR on employees. In an experimental vignette study (N = 136 employees), CSR was manipulated in three degrees (positive, neutral, negative) to examine its effects on job satisfaction, organizational commitment and organizational citizenship behaviour (OCB). In the vignettes, information on distinctiveness, prestige and salience of the out-group were presented. Regression analyses showed that CSR significantly predicted commitment and job satisfaction, but not OCB. We found mediation effects of CSR on commitment, job satisfaction, and OCB through identification, but the effect of CSR on identification explained only little variance which indicates additional underlying mechanisms. The applicability of social identity theory for explaining CSR is discussed. Moreover, we discuss further explaining mechanisms.